2010
DOI: 10.1007/s11274-009-0294-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities and chemical changes during fermentation of sugary Brazilian kefir

Abstract: The microorganisms associated with sugary Brazilian kefir beverage were investigated using a combination of culture-dependent and -independent methods. A total of 289 bacteria and 129 yeasts were identified via phenotypic and genotypic methods. Lb. paracasei (23.8%) was the major bacterial isolate identified, followed by Acetobacter lovaniensis (16.31%), Lactobacillus parabuchneri (11.71%), Lactobacillus kefir (10.03%) and Lactococcus lactis (10.03%). Saccharomyces cerevisiae (54.26%) and Kluyveromyces lactis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
129
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(157 citation statements)
references
References 28 publications
14
129
0
14
Order By: Relevance
“…In our experiment, LAB and TMC reached similar amount of those detected in other sugary kefirs (Sabokbar and Khodaiyan, 2014;Liu and Lin, 2000), with no significant differences between cocci and bacilli (Magalhães et al, 2010). The same findings were achieved by Irigoyen et al (2005) on milk-based kefir after two days, since lactobacilli and lactococci counts were 10 8 cfu/mL.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our experiment, LAB and TMC reached similar amount of those detected in other sugary kefirs (Sabokbar and Khodaiyan, 2014;Liu and Lin, 2000), with no significant differences between cocci and bacilli (Magalhães et al, 2010). The same findings were achieved by Irigoyen et al (2005) on milk-based kefir after two days, since lactobacilli and lactococci counts were 10 8 cfu/mL.…”
Section: Discussionsupporting
confidence: 85%
“…All these microorganisms are embedded in a resilient water-soluble branched glucogalactan matrix named kefiran (Rodrigues et al, 2005;Gulitz et al, 2011;Magalhães et al, 2010). Several of the different bacteria and yeasts that can be found in kefir are recognized as probiotics (Latorre-García et al, 2007;de LeBlanc et al, 2006;Zhou et al, 2009aZhou et al, , 2009b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed this drop to a decrease in lactose amount and a consequent increase in lactic acid content. On the other hand Magalhães et al (2010) reported production of lactic acid during fermentation of kefir is of great importance due to its inhibitory effect on both spoilage and pathogenic microorganisms. So it can be said reduction in pH value moreover leads to increase in total acidity, causes an inhibition of spoilage and pathogenic microorganism growths, too.…”
Section: Resultsmentioning
confidence: 99%
“…The functional properties attributed to kefir include retardation of cancerous tumors, (Murofushi et al 1983;Hosono et al 1990;Hong et al 2009), activation of the immunological system (Osada et al 1994;Vinderola et al 2005), possibility of consumption in cases of lactointolerance, combating of intestinal infections, and antagonistic activity toward pathogenic microorganisms (Hong et al 2009), among others (Zubillaga 2001). Due to its microbiotic constituent, several different substances, which inhibit the growth of pathogenic microorganisms are produced, which are frequently associated with the illnesses of dietary origin (Magalhães et al 2010;Tas et al 2012). These inhibitory substances include hydrogen peroxide and bacteriocins (Helander et al 1997).…”
Section: Introductionmentioning
confidence: 99%